Comparisons of the Physiological and Psychophysical Responses of Handweighted Walking with Three Different Arm Movements in Sedentary Chinese Women: 缺乏運動的女性在步行時配以啞鈴及三種不同擺手方式對生理及自覺歇力程度反應的比較研究 - NG, Robert Siu Kuen (Asian Journal of Physical Education & Recreation, 1999)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. The purpose of this study was to compare the physiological and psychophysical responses during six 20-minute walking sessions at 1.34 m sec-1 and 6% gradient, that employed three different arm movements with and without a 0.45kg hand held weight (HHW) per hand, in fifteen sedentary Chinese college females (mean age = 25.1 ± 1.2 years). The sequence of test sessions was randomized and included two normal arm movements, two vigorous arm movements and two moderate arm pumping, walking with and without a 0.45kg HHW per hand. Dependent variables included oxygen uptake (V02, heart rate (HR) and ratings of perceived exertion (RPE). Statistics used included three, 2-way ANOVA (2 loading conditions x 3 different arm movements) and Tukey's post hoc test. Significant differences were noted between protocols involving hand weights and no hand weights (p<0.05) and among the three different arm movements (p<0.01). However, there were no significant differences with post hoc testing and the interaction. Based on lower RPE values, the minimal influence of the natural gait and the increased exercise intensity, walking with a 0.45kg HHW in each hand, while maintaining moderate arm pumping, was a recommended exercise prescription for sedentary Chinese women. 在香港，步行是一種普遍的活動。本文目的是比較缺乏運動的女性在每秒1.34米(時速3英哩)速度和6%傾斜度的步行機上，步行六次二十分鐘的生理分別。內容包括利用三種擺手方式(自然、急速及大幅度)和兩種手部負重情況(無負重及每隻手各拿一磅啞鈴)，進行運動攝氧量、運動心跳率及自覺歇力的測試，尋找出最能達至訓練效果的步行方式。結果顯示：較佳方式為每隻手拿著一磅啞鈴及大幅度擺手步行法，可建議給經常缺乏運動的女性作為運動指引。